Advances in Digital Signature Algorithms: Performance, Security and Future Prospects - Lyu Shuhan (ITM Web of Conferences)
With the rise of online transactions and digital communications, digital signatures have become essential for verifying document integrity and authenticity across fields like finance, government, and healthcare. This article examines several important digital signature algorithms, analyzing their principles and performance. Each algorithm offers unique advantages: the Rivest – Shamir – Adleman (RSA) provides security through integer factorization, the Digital Signature Algorithm (DSA) through discrete logarithms, and the Elliptic Curve Digital Signature Algorithm (ECDSA) with the efficient elliptic curve cryptography. This paper also discusses recent optimizations, including the Batch and Multi- prime RSA for greater efficiency, the Batch DSA for improved verification speed, and the EdDSA for the enhanced ECDSA performance on Edwards curves. The results show that while optimizations improve computational efficiency, challenges persist, especially with potential quantum threats that could undermine these algorithms' security. Future work should explore hybrid cryptographic schemes and post-quantum cryptography to strengthen digital signature resilience in evolving digital environments.